Diagnostic Accuracy of the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC): An Institution Experience - Karima Rai; Joseph Park; Shamika Gokhale; Fatima Irshaidat; Gurdeep Singh (International Journal of Endocrinology, 2023)
The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) is a standardized system which is used to classify results of thyroid fine-needle aspiration (FNA). This system is used to evaluate and determine which patients should get thyroid surgery. It was created in order to reduce the number of patients requiring surgery. The question remains as to whether this reporting system is accurate in determining those nodules that have malignant potential and those that do not. This study is a retrospective analysis of patients in one institution who have undergone FNA and then thyroid surgery based on TBSRTC. The outcome of the pathology reports after surgery was analyzed to determine the accuracy of TBSRTC in our institution (Lourdes Hospital, Binghamton, NY). The results from our institution were compared with similar studies in other institutions to determine accuracy and reproducibility. Our results indicated that the risk of malignancy in each Bethesda category was similar to the risk percentages described for most categories in the 2017 TBSRTC update.